Core Microstructure and Strain State Analysis in MgB2 Wires with Different Metal Sheaths - C. E. Sobrero; M. T. Malachevsky; A. Serquis (Advances in Condensed Matter Physics)
We present a detailed analysis of the effect of the sheath materials on the microstructure and superconducting properties of MgB2 wires produced by the powder-in-tube method (PIT). We reduced commercial MgB2 powder by attrition milling in nitrogen atmosphere using tungsten carbide balls and obtained powders with grain sizes lower than 150 nm and different strain states through this process. Several Ti, stainless steel, and copper monofilamentary wires were prepared using these powders by the PIT method. We investigated different thermal treatments and mechanical paths during the processing of the wires for the enhancement of the critical currents. The superconducting properties were determined by magnetization measurements in a SQUID magnetometer. The correlation between the thermal treatments, structure, and superconducting properties is discussed.